Establishing the legitimacy of a child between DNA profiling and classical methods of Islamic law - Sarumi, Isa Abdur-Razaq; Ansari, Abdul Haseeb (Serials Publications (P) Ltd., 2017)
Genealogical relationship receives a special attention under Islamic Law that the methods of its establishment and legal proofs for a valid establishment of a child’s legitimacy have been comprehensively defined. These traditional methods remain the sole arbiter whenever disputes arise until the emergence of DNA profiling that almost subverts the hierarchy of the Islamic legal proofs. This paper, therefore, explores the contemporary scholars’ polemics over the position of DNA profiling among other Islamic legal proofs of establishing the legitimacy of children. The paper finds that giving precedence to the traditional methods of establishing a genealogical relationship over DNA would not only safeguard the value of the family institution but also the divine texts. The paper adopts qualitative doctrinal approach by revisiting classical books with the available modern literature.